The Cause Of Trending Topics In Japan - Gede Satya Hermawan (INJECT (Interdisciplinary Journal of Communication), 2023)
The cause of the trending topic on twitter can be found. This paper aims to find this out, using qualitative descriptive methods, by connecting one text to another. On October 19, 2022, 10 topics had more than 20 thousand tweets. After being studied, was found 7 topics discussed entertainment such as the promotion of songs, dramas, or entertainment programs. There is one topic that deals with the sport of baseball. Next, a topic related to news on NHK was also found, and a topic related to a tweet about an article discussing Doujinshi or self-publishing culture in Japan. In addition, it is also found that one topic can refer to different texts. The context itself such as hashtags, images, embedded video or direct link, the bunch of retweets, and others. This paper shows one topic can be trending even though the tweets are not related with the topic itself.